Mapping and analysis of the drug discovery and development process and the underlying uncertainties and the problem of time to market - Kumar, Rachit (2010)
The pharmaceutical industry is one of the most important and fast growing sectors in the world. By the end of year 2010, the global pharmaceutical industry is estimated to grow to $842 billion with a compounded annual growth rate of 6.9% over the period of 5 years. The industry is technologically sophisticated and characterised by highly risky and lengthy processes, intense competition and large research and development expenditures. The key process of the pharmaceutical industry constitutes of the drug discovery and development process which takes nearly 10 to 15 years for development from the earliest stage in discovery to the time it is made available for use to the patients and costs an average of $800 million. Despite successfully translating discoveries into successful products, the process is plagued by increasing number of uncertainties which leads to an increased developmental time cycles. This delays the product‟s entry into the market thereby causing heavy losses to the pharmaceutical industry. This research presents techniques that enable pharmaceutical firms to reduce uncertainties as well as tackle the problem of time to market with a view to improving the product quality thereby increasing their profits significantly.